ANALISIS LAPORAN KEUANGAN PT. KALBE FARMA, TBK (PERIODE 2022 – 2023) - umi arifah; Teguh Widiatmoko; Sri Hermuningsih (LPPM Akademi Manajemen Administrasi Yogyakarta, 2025)
The purpose of this article is to determine the financial performance of PT. Kalbe Farma Tbk based on the liquidity ratio, profitability ratio and solvency ratio and activity ratio in 2022-2023. The results of the analysis show that the financial performance of PT. Kalbe Farma Tbk is quite good. However, overall, the comparison of financial performance in the post-covid-19 pandemic period tends to decline because it is in a transition period to grow and recover again. Based on the results of the analysis, the author provides several for PT. Kalbe Farma Tbk to pay more attention to sales policies, asset management, maximizing receivables collection, and inventory so that the company's goals can be achieved optimally and all operational activities of the company can run according to company regulations. In addition, PT. Kalbe Farma Tbk must strengthen communication and routinely conduct periodic evaluations of the company's financial performance achievements with the hope that the company's policies that are set are truly in accordance with the company's real conditions so that they can generate an increase in net profit every year.